Contextual learning concepts - Nada, Qotrun; Sa’adah, Siti Nur Juliati (Maliki Interdisciplinary Journal, 2024)
Today, learning systems that have a theoretical nature can still be found in various educational environments today. What happens is that the majority of students experience difficulties and do not even get the meaning conveyed so that they can apply it in everyday life. From this it can be seen that it is clear evidence that the majority of students cannot easily connect what they have learned at school with the use of science in everyday life. Therefore, to deal with this condition, teaching staff must have the ability to design a learning system that can later be used as a provision for students both in theoretical and practical knowledge. Educators are also required to be smarter in creating learning space situations that can make it easier for students to understand the meaning and relate to the lesson material they have learned.